ANALYZING PATTERN OF DEATH DUE TO BLUNT FORCE TRAUMA IN INDORE REGION : ONE YEAR RETROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2019)
Deaths resulting from blunt force trauma are some of the most common cases encountered by the practicing forensic pathologist. For instance, almost all transportation fatalities (including those involving motor vehicle collisions, pedestrians being struck by vehicles) and other deaths like jumping or falling from heights result from blunt force trauma. Blunt-force injuries are produced by a variety of objects in which some of them produce distinctive patterns of injury of potential evidentiary value. The present 01 Year retrospective study was carried out in the Department of Forensic Medicine & Toxicology, M.G.M. Medical College & M.Y. Hospital, Indore during the period from January 2017 to December 2017. During this period out of total 2197 cases, 896 cases with alleged history of deaths due to blunt force trauma were brought to the mortuary of the hospital for medico-legal postmortem examination. The objective of the study was to understand various pattern of death due to blunt force trauma, mode of injury, different types of fracture associated with the trauma and demographic profile of deceased so as steps can be taken not only to minimize the mortality but also to prevent and reduce their incidence at least in cases where human errors plays a role.
Keywords: Blunt Force Trauma; Fractures; mode of injury; demographic profile